The Influence of Non-Performing Loan (NPL) and Debt to Equity Ratio (DER) on Return on Assets (ROA) with Good Corporate Governance (GCG) as a Moderating Variable in State-Owned Banks in Indonesia - Inda Novita Sari; Renny Maisyarah; M. Irsan Nasution (Utan Kayu Publishing, 2025)
This study aims to analyze the effect of Non-Performing Loans (NPL) and Debt-to-Equity Ratio (DER) on bank performance, measured by Return on Assets (ROA), and to examine the moderating role of Good Corporate Governance (GCG) in these relationships. The data used in this study comes from the annual reports and sustainability reports of Indonesian state-owned banks (HIMBARA), including Bank Mandiri, BRI, BNI, and BTN, covering the period from 2022 to 2024. The methodology employed is panel data regression with Moderated Regression Analysis (MRA). The results show that NPL has a significant negative effect on ROA, confirming that an increase in non-performing loans reduces the profitability of banks. Conversely, DER does not show a significant effect on ROA, suggesting that the debt-based funding structure does not directly influence the profitability performance of HIMBARA banks. Additionally, GCG proves to have a significant moderating role in weakening the negative impact of NPL on ROA, while GCG does not moderate the relationship between DER and ROA. This study contributes practical insights for regulators and bank management to strengthen corporate governance to maintain stability and enhance profitability, especially when facing increased credit risk